A Case of Raoultella Planticola Pneumonia as A Complication of Retroperitoneal Abscess in Immunocompetent Patient - Abdelhamy, Adel; Aljaser, Fahd; Zayed, Ahmed; Hetata, Dina (British Journal of Healthcare and Medical Research, 2024)
Raoultella Planticola (R. Planticola) is a gram-negative bacillus with much similarity to Klebsiella, it is a rare cause of Pneumonia. rare cases has been reported with R.Planticola like abscess pancreatitis and necrotizing fasciitis. To our knowledge we report the first case of Raoultella Planticola retro peritoneal collection complicated by Raoultella Planticola Pneumonia in Kuwait.